TINJAUAN FAKTOR KETERLAMBATAN PENGAJUAN KLAIM PASIEN RAWAT INAP KE BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN DI RSU UNIVERSITAS KRISTEN INDONESIA - Sya'diah,SST,MKes., Yayah (APIKES Bhumi Husada Jakarta, 2024)
The implementation of Vedika Digital Claim Verification for Advanced Referral Health Facilities has facilitated the verification process of claims submitted by hospitals through a digital application managed by the Health Social Security Agency on Health. The integration of Vedika has resulted in enhanced participant satisfaction by improving service delivery. This research aims to investigate the factors contributing to delays in the submission of inpatient claims to BPJS Kesehatan at UKI Hospitals, with a focus on the 5M factors: Man, Method, Material, Machine, and Money. The research methodology employs a mixed-method approach to analyze inpatient claims, incorporating quantitative analysis using the Slovin formula on a sample of 87 patient claim statuses, and qualitative descriptive analysis involving six inpatient case-mix personnel. The findings reveal that a significant proportion of claim files are incomplete (93.1%). The qualitative analysis highlights issues related to the Standard Operating Procedures for inpatient claim management, particularly the synchronization of diagnosis and supporting data. Challenges include discrepancies in diagnosis codes and medical procedures, which require confirmation with the respective doctors, thereby affecting the hospital's operational stability regarding claims. The study recommends conducting periodic performance reviews of personnel involved in BPJS Kesehatan claims to assess claim completeness and evaluate the accuracy of BPJS claim file inputs. Keywords: Social Security Agency on Health, Delayed Claim Submission